2021
DOI: 10.3390/pathogens10101238
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Modeling of Spiramycin against Mycoplasma synoviae in Chickens

Abstract: This research aimed to assess the pharmacokinetics/pharmacodynamics (PK/PD) and tissue residues of spiramycin in chickens. The PK of spiramycin were determined in 12 chickens using a parallel study design in which each group of chickens (n = 6) received a single dose of spiramycin at 17 mg/kg intravenously (IV) or orally. Plasma samples were collected at assigned times for up to 48 h to measure spiramycin concentrations. Additionally, a tissue depletion study was performed in 42 chickens receiving spiramycin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In this study, we confirmed the possibility of applying an old weapon, spiramycin, to various inflammatory diseases, the new enemy. Spiramycin has been shown to exhibit anti-bacterial, anti-viral, and anti-parasitic activities [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, no study has reported the anti-inflammatory potential of spiramycin in LPS-induced macrophage RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we confirmed the possibility of applying an old weapon, spiramycin, to various inflammatory diseases, the new enemy. Spiramycin has been shown to exhibit anti-bacterial, anti-viral, and anti-parasitic activities [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, no study has reported the anti-inflammatory potential of spiramycin in LPS-induced macrophage RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Spiramycin is a 16-membered ring macrolide antibiotic that was first discovered 70 years ago in a culture medium of Streptomyces ambofaciens in 1952 ( Figure 1 ). The antibiotic action of spiramycin, which inhibits protein synthesis in bacterial cells during translocation, has high antimicrobial activity against Gram-positive bacteria and mycoplasma species, and is widely used to treat toxoplasmosis and other soft-tissue infections in cattle, pigs, poultry, and sheep [ 6 , 7 , 8 ]. Spiramycin is prescribed in some countries for various odor-causing infections including periodontitis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%